FRI0232 Treatment with angiotensin II receptor-blockers is associated with lower relapse rate and reduced duration of treatment in patients with giant cell arteritis. (23rd January 2014) - Alba, M.A.; García-Martínez, A.; Espigol-Frigole, G.; Tavera-Bahillo, I.; Prieto-González, S.; Corbera-Bellalta, M.; Planas-Rigol, E.; Hernández-Rodríguez, J.; Cid, M.C.
Abstract : Background: Nearly 90% of patients with giant cell arteritis (GCA) experience adverse effects related to long-term corticosteroid (CS) treatment. Search for CS-paring agents has been disappointing and only methotrexate has been demonstrated to have modest effect in a meta-analysis of randomized clinical trials. Recently, angiotensin converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARB) have been demonstrated to have anti-inflammatory properties. Objectives: The purpose of this study was to determine whether concomitant treatment with ACEI or ARB is associated with changes in the clinical course of patients with GCA. Methods: Retrospective study of 94 patients (24 males, 70 females) with biopsy-proven GCA, prospectively screened for aneurysm development and treated by the authors during 5.4±1.4 years (3.8-10.5). Patients were grouped based on their treatment: ACEI (group 1), ARB (group 2) or no ACEI/ARB (group 3). Number of recurrences, time in weeks to reach a stable prednisone dose <10 mg/day with no relapses and aneurysm development were compared among the 3 groups. Chi-square test, ANOVA test and Kaplan-Meyer survival analysis/long-rank test were used for statistical comparison. Results: During follow-up, 31 patients were treated with ACEI, 12 with ARB and 51 did not receive any of these medications. Patients in the group receiving ARB presented lower frequency of relapses than the other two groups (ARB 25% vs ACEI 61% vs not treated 67%, p=0.021). Patients who had received an ARB required 27±22 weeks to reach a maintenance prednisone dosage <10 mg/day in comparison to 78±82 weeks for patients who received ACEI and 77±88 weeks for patients not treated with ACEI/ARB (p=0.001). We found no differences between groups in the frequency of aneurysm development. Conclusions: Patients treated with ARB present less frequently relapses and require less time to reach a stable prednisone dose <10 mg day. The possible corticosteroid sparing effect of these agents should be tested in prospective studies. References: Andersson R, Malmvall BE, Bengtsson BA. Long-term corticosteroid treatment in giant cell arteritis. Acta Med Scand. 1986;220(5):465-9. Proven A, Gabriel SE, Orces C, O'Fallon WM, Hunder GG. Glucocorticoid therapy in giant cell arteritis: duration and adverse outcomes. Arthritis Rheum. 2003;49(5):703-8. Mahr AD, Jover JA, Spiera RF, Hernandez-Garcia C, Fernandez-Gutierrez B, Lavalley MP, et al. Adjunctive methotrexate for treatment of giant cell arteritis: an individual patient data meta-analysis. Arthritis Rheum. 2007;56(8):2789-97. Disclosure of Interest: None Declared